2019
DOI: 10.1136/ijgc-2019-000848
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of enhanced recovery after laparotomy in gynecologic oncology

Abstract: IntroductionEnhanced recovery after surgery (ERAS) pathways combine a comprehensive set of peri-operative practices that have been demonstrated to hasten patient post-operative recovery. We aimed to evaluate the adoption of ERAS components and assess attitudes towards ERAS among gynecologic oncologists.MethodsWe developed and administered a cross-sectional survey of attending, fellow, and resident physicians who were members of the Society of Gynecologic Oncology in January 2018. The χ2 test was used to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…At present, there are large differences in reports on the incidence of DVT after gynecological diseases. The incidence of DVT after gynecological surgery ranges from 11 to 29% [1,10]. Sakon et al [11] have pointed out that DVT occurred after gynecological surgery, the incidence of DVT can be as high as 17.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are large differences in reports on the incidence of DVT after gynecological diseases. The incidence of DVT after gynecological surgery ranges from 11 to 29% [1,10]. Sakon et al [11] have pointed out that DVT occurred after gynecological surgery, the incidence of DVT can be as high as 17.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the continuous improvement of surgical technology and the improvement of surgical instruments and equipment, deep vein thrombosis (DVT) of the lower extremities is still one of the common complications after gynecological surgery [1]. The feared complication of DVT is pulmonary embolism, which is closely associated with higher mortality and poorer prognosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, despite the clinical bene ts of early resumption of oral intake, its implementation in clinical practice has been relatively "delayed". Possible reasons include a lack of convincing data, a lowlevel understanding of ERAS, and limitations in institutional experience and systems (19). Therefore, in an effort to identify di culties in the implementation of early postoperative oral intake programs, we carried out a nationwide survey to determine clinical practices and attitudes toward the postoperative resumption of oral intake among all clinical practitioners along with their level of understanding of ERAS.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, 27 guidelines have been developed for different clinical scenarios using the principles of physiological homeostasis, 4 and have been associated with improved outcomes in other surgical specialities, such as urologic, thoracic and orthopedic surgery 5‐8 . The first gynecologic oncology guidelines were published in 2016 9 and revised in 2019 10 ; they consist of 16 elements and have been purportedly adopted across North America 11 . Practice surveys from Europe, America and Australia/New Zealand have however shown that while certain elements of the ERAS pathways such as antibiotic prophylaxis and hypothermia prevention are now standard of care within the gynecologic oncology community, others, such as shortened fasting times, avoidance of nasogastric tubes or carbohydrate loading, have not been widely adopted 11‐13 …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The first gynecologic oncology guidelines were published in 2016 9 and revised in 2019 10 ; they consist of 16 elements and have been purportedly adopted across North America. 11 Practice surveys from Europe, America and Australia/New Zealand have however shown that while certain elements of the ERAS pathways such as antibiotic prophylaxis and hypothermia prevention are now standard of care within the gynecologic oncology community, others, such as shortened fasting times, avoidance of nasogastric tubes or carbohydrate loading, have not been widely adopted. [11][12][13] In keeping with the provincial call for implementation of a…”
Section: Introductionmentioning
confidence: 99%